Ganirelix and the prevention of premature luteinizing hormone surges - Bernadette Mannaerts, Ph.D (Elsevier, 2023)
Ganirelix is a gonadotropin-releasing hormone (GnRH) antagonist with high antagonistic activity that blocks the GnRH receptor by competitive binding. A daily dose of 0.25 mg of ganirelix was sel5ected after a phase II study because it was the minimal, effective daily dose to prevent premature luteinizing hormone surges and this dose yielded the highest ongoing pregnancy rate per started cycle. After subcutaneous administration, ganirelix is rapidly absorbed, reaching peak levels within 1-2 hours (tmax), and has a high absolute bioavailability (>90%). Prospective, comparative studies have demonstrated the advantages of GnRH antagonists over long GnRH agonist treatment in assisted reproduction, including the immediate reversibility of drug effects, a requirement for less follicle-stimulating hormone, a shortened duration of stimulation, a reduced incidence of ovarian hyperstimulation syndrome, and reduced patient burden. Combined analyses concluded that in the general in vitro fertilization population, there is a trend for a slightly lower ongoing pregnancy rate and a lower risk of ovarian hyperstimulation syndrome that is largely eliminated when considering triggering with GnRH agonist instead of human chorionic gonadotropin. Regardless of all the research, it is still not fully elucidated why the long GnRH agonist protocol has a trend for higher pregnancy rates after fresh transfer of the same number of good-quality embryos.